2013
DOI: 10.1093/bja/aet206
|View full text |Cite|
|
Sign up to set email alerts
|

Neuropathic pain: a pathway for care developed by the British Pain Society

Abstract: Neuropathic pain is a common chronic pain condition that can be challenging to treat, particularly for non-specialists. The development of the Map of Medicine care pathway for the management of neuropathic pain was led by the British Pain Society. Focusing on treatment by non-specialists, this pathway is based on new evidence, consensus, and the interests of service users. This paper presents the care pathway and accompanying evidence base, highlighting its salient features, and discussing important treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…There are several international manuscripts about the organization and delivery of pain services that could be used as a guidance for improving pain management (28)(29)(30)(31)(32). Educational activities in most pain clinics in Croatia focus on providing educational materials for patients developed by pharmaceutical companies, and less frequently on educational materials developed by the Croatian Association for the Treatment of Pain or employees of the clinics.…”
Section: Discussionmentioning
confidence: 99%
“…There are several international manuscripts about the organization and delivery of pain services that could be used as a guidance for improving pain management (28)(29)(30)(31)(32). Educational activities in most pain clinics in Croatia focus on providing educational materials for patients developed by pharmaceutical companies, and less frequently on educational materials developed by the Croatian Association for the Treatment of Pain or employees of the clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, consensus guidelines for neuropathic pain have been adapted for treatment of pain in SFN 2. Pragmatic consensus guidelines include those of the UK's National Institute of Health and Care Excellence and the Map of Medicine 56. This usually involves first-line treatment with gabapentinoids, gabapentin or pregabalin (that bind to α 2 δ 1 and alter trafficking of voltage-gated calcium channels), tricyclic antidepressant (unlicensed indication) or serotonin-norepinephrine reuptake inhibitor (licensed for painful diabetic neuropathy).…”
Section: Managementmentioning
confidence: 99%
“…The estimate of the annual cost of chronic pain was greater than the annual costs of heart disease ($309 billion), cancer ($243 billion), and diabetes ($188 billion) [2]. Neuropathic pain is a common chronic pain condition [3] that is caused by peripheral nerve injury and is characterized by long-lasting exaggerated pain behavior such as allodynia and hyperalgesia [4]. Although neuropathic pain is known as a particularly unpleasant type of pain [3], the management of patients with neuropathic pain is challenging because of the multiplicity of mechanisms involved in neuropathic pain conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain is a common chronic pain condition [3] that is caused by peripheral nerve injury and is characterized by long-lasting exaggerated pain behavior such as allodynia and hyperalgesia [4]. Although neuropathic pain is known as a particularly unpleasant type of pain [3], the management of patients with neuropathic pain is challenging because of the multiplicity of mechanisms involved in neuropathic pain conditions [5]. Precise pathophysiological mechanisms of neuropathic pain are still unclear, however, a number of studies have suggested that microglial activation and inflammatory cytokines in the spinal cord play important roles in the development and maintenance of neuropathic pain [6,7].…”
Section: Introductionmentioning
confidence: 99%